Atorvastatin Attenuates Endothelial Cell Injury in Atherosclerosis Through Inhibiting ACSL4-Mediated Ferroptosis - Huilian Tan; Ling Liu; Yanchao Qi; Dahong Zhang; Yanchun Zhi; Yu Li; Huimin Zhang; Jun Liu (Cardiovascular Therapeutics)
Conclusion: Our findings suggest that ATV attenuates endothelial cell injury in AS by inhibiting ACSL4-mediated ferroptosis. These results provide insights into the potential therapeutic strategies for the treatment of AS.